Synthesis and Structural Studies of Co(II), Ni(II), Zn(II) and Cd(II) Metal Complexes of 2-Hydroxy-5- Methyl Benzene-1,3-bis-(Carbalidine-2-Amino Thiazole) - Sharma, R.C.; Singh, Shubhra; Kumar, D.; Vats, Ritika (Asian Journal of Chemistry, 2010)
Some new metal complexes of Co(II), Ni(II), Zn(II) and Cd(II) of 2-hydroxy-5-methyl benzene-1,3-bis-(carbalidine-2-amino thiazole) have been synthesized. All complexes and ligands are characterized on the basis of their repeated melting point determination, TLC, elemental analysis, conductance measurements, magnetic susceptibilty measurement, UV and IR spectra data.